Axiology of Electronic programs in updating the methodology of information and communication sciences Tropes 8.4 Case Study - Batahr, Hisham (ALBAHITH ALALAMI, 2018)
The study aims to display the scientific benefit offered by modern electronic programs for various scientific research methods, while determining the positive scientific role played by these programs in modernizing the methodologies and logic of scientific thinking, especially with the rapid development of the sciences and their curricula. These programs link accurately with scientific results. The importance of the study is to provide practical mechanisms to highlight the scientific projection of the electronic programs in various steps of scientific research. A case study was used for Tropes version 8.4, which analyzes written, audio and visual semantic texts and presents a set of statistical results that facilitate the difficulties of systematic research in front of the researcher. This program is tested on a set of studies to demonstrate its axiology.